Molecular Analysis of Klebsiella Pneumoniae Isolates Collected from Sputum Samples in Duhok Iraq - Turki Monawer, Alaa' (Al-Nahrain Journal of Science, 2025)
Klebsiella is an important human pathogen that may lead to both community-acquired infections and nosocomial infection. A major threat to public health is the increasing frequency of Klebsiella pneumoniae strains that are resistant to drugs. This study aimed to determine the frequency of K. pneumoniae in sputum samples obtained from patients at the Azadi Teaching Hospital in Duhok City, Iraq, as well as the 16S rRNA and rpoB genes for molecular analysis of K. pneumoniae. Eighty-three sputum samples were collected from patients at the Azadi Teaching Hospital in Duhok, Iraq, between January and May of 2024. Through morphologic and biochemical investigations, the isolates were identified. Klebsiella pneumoniae isolates were isolated from 37/83 (44.6%) sputum samples. Upon molecular examination, every isolate in our investigation displayed a PCR result of 108 bp using the K. pneumonia specific primer (rpoB), and they were able to generate a 16S rRNA gene of 1500 bp amply. Finding out how often K. pneumonia infections are among patients at Azadi Teaching Hospital in Duhok City, Iraq, is a crucial goal of this study.